An electrochemical device generating metal ion adducts of organic compounds for electrospray mass spectrometry. (1st September 2016) - Jaklová Dytrtová, Jana; Jakl, Michal; Navrátil, Tomáš; Cvačka, Josef; Pačes, Ondřej
Graphical abstract: Highlights: Electrochemical device connectable prior electrospray ionization mass spectrometer. Activation of organics by the electrochemical generation of reactive metal cations. Easy switching of different working electrodes via rotatable segment of the device. Applicable for non-polar organics as well as for organics in complicated matrices Abstract: An electrochemical device enabling selection of the working electrode was developed to be hyphenated with a mass spectrometer equipped with an electrospray. The device contains a rotatable block (carousel) with three ports for working electrodes, which can be easily chosen (changed) by a rotation of the carousel. The method takes advantage of the high reactivity of electrochemically generated metallic ions "in statu nascendi" . The device is suitable for ionization of various organic compounds (e.g., lipids, lipoproteins, pesticides, drugs, metabolites, lipids, lipoproteins) in biological and other matrices. The wide range of applications is made possible by the selection from three different solid electrodes placed in the carousel. This technical upgrade allows providing a number of possible chemical adducts and hereby the method can be tailored according to specific demands. The applicability of the electrochemical device is demonstrated by the electrochemical activation of pesticide cyproconazole (Cyp) in a soil solution matrix via formation of its adducts with Ag and Cu cations, generated from the working electrode material. The metal/Cyp adducts are on-line detected using an electrospray ionization mass spectrometer.